3D Printing Plasmonic-Enhanced Sulfurized Polyacrylonitrile Cathodes for High-Energy Li–S Microbatteries - Liu, Yu; Fu, Penghao; Qiu, Jieshan; Wang, Zhiyu (Nano-Micro Letters, 2026)
The rapid expansion of the Internet of Things (IoT) has fueled the demand for high-energy, compact microbatteries capable of powering energy-demanding IoT devices in small, flexible formats. Li–S batteries offer a promising solution but suffer from more intense polysulfide (LiPS) shuttling in the limited volume of microbatteries. Here, we achieved a high-energy quasi-solid-state Li–S microbattery by employing 3D-printed hierarchically structured sulfurized polyacrylonitrile (3D-HSPAN) cathodes with plasmonic enhancement. The direct ink writing technique produces shape-customizable 3D-HSPAN cathodes with precise architectural engineering, ultra-high mass loading up to 37.1 mg cm−2, and greatly improved ionic transport. Plasmonic MXene is harnessed to further boost LiPS-free redox conversion through synergistic photothermal effect and hot-carrier injection under near-infrared irradiation. Paired with a LiNO3 sustained-release carbonate-based gel polymer electrolyte, such quasi-solid-state Li–S microbatteries deliver high areal capacities over 18.1 mAh cm−2 and exceptional areal energy density reaching 30.7 mWh cm−2. Their versatility in flexible, transparent, and shape-customizable formats is demonstrated for wearable electronics and low-temperature operation. This work establishes a framework for uniting additive manufacturing, high-energy redox chemistry, and light-harvesting strategies to advance energy solutions. Highlights: 1 The DIW technique fabricates shape-customizable 3D-printed hierarchically structured sulfurized polyacrylonitrile (3D-HSPAN) cathodes with precisely controlled scaffolds and ultra-high mass loading up to 37.1 mg cm−2. 2 Plasmonic MXene further regulates the redox kinetics of solid-state sulfur chemistry for 3D-HSPAN cathode via synergistic photothermal effect and hot-carrier injection. 3 The quasi-solid-state Li–S microbattery delivers an exceptional areal capacity of 18.1 mAh cm−2 and a high areal energy density of 30.7 mWh cm−2.